(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The article reveals information about the most common allergic diseases among children today. Allergic asthma in children has been reported to occur as a result of adverse effects in the environment, heavy activities, and certain changes in the respiratory tract. The importance of air and nature in the treatment of this disease, the types of treatment of respiratory organs are given with scientific theoretical basis.